Ag-doped 45S5 Bioglass-based bone scaffolds by molten salt ion exchange: processing and characterisation - Newby, P. J.; El-Gendy, R.; Kirkham, J.; Yang, X. B.; Thompson, I. D.; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2011)
There is increasing interest in developing scaffolds with therapeutic and antibacterial potential for bone tissue engineering. Silver is a proven antibacterial agent which bacteria such as MRSA have little or no defense against. Using an ion exchange method, silver ions have been introduced into 45S5 Bioglass̄ based scaffolds that were fabricated using the foam replication technique. This technique allows the introduction of Ag+ ions onto the surface of the scaffold without compromising the scaffold bioactivity and other physical properties such as porosity. Controlling the amount of Ag+ ions introduced onto the surface of the scaffold was achieved by tailoring the ion exchange parameters to fabricate samples with repeatable and predictable Ag+ ion release behavior. In vitro studies in simulated body fluid were carried out to ensure that the scaffolds maintained their bioactivity after the introduction of Ag+ ions. It was also shown that the addition of low concentrations (2000:1 w/w) of silver ions supported the attachment and viability of human periodontal ligament stromal cells on the 3D scaffolds. This work has thus confirmed ion exchange as an effective technique to introduce Ag+ ions into 45S5 Bioglass̄ scaffolds without compromising the basic properties of 45S5 Bioglass̄ which are required for applications in bone tissue engineering. © Springer Science+Business Media, LLC 2011.
UnivIS-Import:2015-03-09:Pub.2011.tech.IW.LM.agdope_3